Citizenship Seen from Islamic-Christian Compared Religious Social Thought - Villagrán, Gonzalo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2019)
Citizenship, meaning belonging to a political community, is a concept of secular origin, fruit of the Western modernity and a key for a healthy distinction between religion and politics. Nevertheless, religious traditions can help to get a deeper understanding of this concept. From a comparative theology perspective, the tradition of secular political thought and Christian and Muslim traditions of political thought have a lot to learn from each other. On the one hand, Christianity and Islam can be enlightened from the secular idea of citizenship as a way to deepen in a just differentiation between religion and politics. On the other hand, both religious traditions, each one in its own way, help the secular tradition to look at the human being as whole, including its religious dimension, as well as to understand the concept of citizenship as open to the reality of the entire human family.
Keywords: citizenship; State; nation; human dignity; umma; social teaching; laicity; compared theology